2014
DOI: 10.1007/s00421-014-2832-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prior eccentric exercise on heavy-intensity cycling: the role of gender and oral contraceptives

Abstract: The preservation of exercise tolerance during heavy-intensity cycling performed after intense eccentric exercise is improved in women compared to men. Furthermore, the preservation of exercise tolerance is exclusive to 17β-estradiol and cannot be replicated with an exogenous synthetic estrogen replacement delivered in an oral contraceptive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Although torque loss is regarded as the most functional measure of EIMD (Warren et al 1999), in agreement with previous research (Joyce et al 2014; Minahan et al 2015; Roth et al 2001), the current study reported ΔCK peak to be significantly higher in OCP users (low oestrogen levels) compared to non-users (high oestrogen levels) following EIMD. Although Joyce et al (2014) and Minahan et al (2015) reported CK levels to be significantly higher in OCP users compared to non-users, they only monitored CK up to 48 h post-EIMD despite peak CK characteristically occurring at 96 h post-EIMD (Hyatt and Clarkson 1998).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Although torque loss is regarded as the most functional measure of EIMD (Warren et al 1999), in agreement with previous research (Joyce et al 2014; Minahan et al 2015; Roth et al 2001), the current study reported ΔCK peak to be significantly higher in OCP users (low oestrogen levels) compared to non-users (high oestrogen levels) following EIMD. Although Joyce et al (2014) and Minahan et al (2015) reported CK levels to be significantly higher in OCP users compared to non-users, they only monitored CK up to 48 h post-EIMD despite peak CK characteristically occurring at 96 h post-EIMD (Hyatt and Clarkson 1998).…”
Section: Discussionsupporting
confidence: 91%
“…Although Joyce et al (2014) and Minahan et al (2015) reported CK levels to be significantly higher in OCP users compared to non-users, they only monitored CK up to 48 h post-EIMD despite peak CK characteristically occurring at 96 h post-EIMD (Hyatt and Clarkson 1998). By measuring CK at 96 and 168 h post-EIMD, the current study reduces the chance of missing a true peak in CK and can therefore confirm that ΔCK peak is significantly higher in OCP users compared to non-users post-EIMD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations